Joint Resource Allocation Algorithms for Full-Duplex Wireless Cellular System - Liu, Fang; Liu, Zhongsheng; Bai, Yong (Wireless personal communications, 2017)
In the full-duplex wireless cellular system, co-channel interference may limit the achieved cell throughput, and proper radio resource allocation can help to reduce the co-channel interference. In this paper, joint resource allocation on user pairs and resource blocks (RBs) in full-duplex OFDMA cellular system is investigated for benefiting system throughput or user fairness. Firstly, a binary-integer programming optimization problem for maximizing cell throughput is formulated and the optimal solutions are given by exhaustive search. Then, two suboptimal heuristic algorithms are proposed to ease the implementation in practical wireless cellular system. The effectiveness of the proposed algorithms are verified by system level simulations in a full-duplex single cellular system.